2017
DOI: 10.3389/fnut.2017.00026
|View full text |Cite
|
Sign up to set email alerts
|

A Dairy Herd Case Investigation with Very Low Dietary Cation–Anion Difference in Prepartum Dairy Cows

Abstract: During the periparturient period, subclinical hypocalcemia (total plasma Ca concentration <2.0 mmol/l) is a potential problem for the dairy cow; consequently, its prevention is essential for success of fertility and productive performance. Dietary cation–anion difference (DCAD) has been defined as the difference in milliequivalents of cations (Na, K) and anions (Cl, S) per kilogram of dry matter (DM) and has a direct impact on blood acid–base metabolism. Diets rich in K and Na induce metabolic alkalosis, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Our results showed that all plasma levels of Glc, UN, ALT, AST, AKP, TP, Alb, SOD, GSH-Px, MDA, and CAT were unaffected by DCAD variation. This is supported by a previous study of Melendez and Poock [ 9 ], who reported that lowering DCAD had little effect on blood Alb. Our previous study also found that DCAD levels (+300, +150, 0, and −150) had no significant effect on plasma GSH-Px or MDA content in female goats [ 38 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results showed that all plasma levels of Glc, UN, ALT, AST, AKP, TP, Alb, SOD, GSH-Px, MDA, and CAT were unaffected by DCAD variation. This is supported by a previous study of Melendez and Poock [ 9 ], who reported that lowering DCAD had little effect on blood Alb. Our previous study also found that DCAD levels (+300, +150, 0, and −150) had no significant effect on plasma GSH-Px or MDA content in female goats [ 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…The DCAD level has been an important parameter in the process of formulating diets fed to Holstein cows in recent years [ 3 , 4 , 5 , 6 , 7 ]. Studies have shown that diets with a lower DCAD could enhance health and extend the economic life of transition mammary animals [ 8 , 9 , 10 ]. Recently, attention has been given to the interaction of DCAD with calcium (Ca) [ 11 ], cholecalciferol/calcidiol [ 12 ], 5-hydroxy-l-tryptophan [ 13 ], vitamin D [ 14 , 15 , 16 ], and the duration [ 17 , 18 ] of blood Ca level increases.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by previous study. Melendez and Poock [9] reported that lowering DCAD had little effect on blood Alb. Wu et al [67] found that DCAD level (+ 300, + 150, 0, and − 150) had no signi cant effect on plasma GSH-Px and MDA content in female goats.…”
Section: Discussionmentioning
confidence: 99%
“…The DCAD level has been an important parameter in the process of formulating diets in recent years [3][4][5][6][7]. Studies have shown that diets with a lower DCAD could enhance the health and extend the economic life of transition mammary animals [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It is the decrease in blood calcium (Ca) level due to rapid drain of Cite as : Cariappa, A G Adeeth and Chandel, B S and Sankhala, Gopal and Mani, Veena and R, Sendhil and Dixit, Anil Kumar and Meena, B S, Prevention Is Better Than Cure: Experimental Evidence From Milk Fever Incidence in Dairy Animals of Haryana, India (May 23, 2021). DOI: 10.2139/ssrn.3851561 Ca into colostrum after parturition (calving) (Melendez and Poock 2017;Rodríguez, Arís and Bach 2017). As Ca is essential for organs which has smooth muscle functions like uterus, abomasum, teat sphincter and rumen; the deficiency of Ca or MF affects these organs hampering fertility and productive performance (Melendez et al 2019;Caixeta et al 2017).…”
Section: Introductionmentioning
confidence: 99%